2022
DOI: 10.3390/sym14071477
|View full text |Cite
|
Sign up to set email alerts
|

A Symmetrical Terahertz Triple-Band Metamaterial Absorber Using a Four-Capacitance Loaded Complementary Circular Split Ring Resonator and an Ultra-Thin ZnSe Substrate

Abstract: In this research work, a symmetrical four-capacitance loaded complementary circular split ring resonator is proposed, which uses an ultra-thin Zinc Selenide (ZnSe) substrate to realize a low-profile triple-band metamaterial (MTM) perfect absorber for application in the terahertz (THz) frequency range. The electromagnetic properties of the proposed structure were calculated and investigated using the Finite Integration Technique (FIT). The proposed structure exhibited three highly absorptive (nearly perfect) pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…As a result, the absorption response shows red shift phenomenon as the h s and a increases 15 . Table 4 compares previously reported studies 10,11,13,15,28,[46][47][48] with proposed MMA in terms of unit cell size, thickness, and resonating frequencies, indicating that the proposed MMA has seven absorption peaks with compact metallic structure, which is superior to previously reported MMA.…”
Section: Resultsmentioning
confidence: 80%
“…As a result, the absorption response shows red shift phenomenon as the h s and a increases 15 . Table 4 compares previously reported studies 10,11,13,15,28,[46][47][48] with proposed MMA in terms of unit cell size, thickness, and resonating frequencies, indicating that the proposed MMA has seven absorption peaks with compact metallic structure, which is superior to previously reported MMA.…”
Section: Resultsmentioning
confidence: 80%
“…A triple‐band metamaterial absorber using a symmetrical four‐capacitance loaded complementary circular split ring resonator has been presented in Abdulkarim et al 12 The design demonstrates the perfect absorption at three resonance frequencies. Additionally, it has been reported that the absorber is not affected by polarization and incident wave angles.…”
Section: Introductionmentioning
confidence: 99%
“…Various examples of these structures can be found in [6][7][8][9]. Noteworthy, the recently emerged structures of absorbers are based on metamaterial structures.…”
Section: Introductionmentioning
confidence: 99%